Speech, Language, Hearing, and Otopathology Results From the International Smith--Magenis Syndrome Patient Registry. - Brennan, Christine; Smith, Mara Louise; Baiduc, Rachael R.; O'Connor, Liam (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Smith--Magenis syndrome (SMS), a rare, genetically linked complex developmental disorder caused by a deletion or mutation within chromosome 17p11.2, is associated with delays in speech-language development, otopathology, and hearing loss, yet previous studies lack comprehensive descriptions of hearing and communication profiles. Here, analyses of patient registry data expand what is known about speech, language, hearing, and otopathology in SMS. Method: International speech-language and hearing registry survey data for 82 individuals with SMS were analyzed using descriptive and inferential statistics. Hearing loss, history of otitis media and pressure equalization (PE) tubes, communication mode, expressive/receptive language, and vocal quality were analyzed for all subjects and subjects grouped by age. Statistical methods included descriptive statistics and Pearson's chi-square tests of independence to test for differences between age groups for each variable of interest. Association analyses included Pearson's correlations. Results: Hearing and otological analyses revealed that 35% of subjects had hearing loss, 66% had a history of otitis media, and 62% had received PE tubes. Speech-language analyses revealed that 60% of subjects communicated using speech, 79% began speaking words at/after 24 months of age, 92% combined words at/after 36 months, and 41% used sign language before speech. There was a significant association between the age that first words were spoken and the age that PE tubes were first placed. Communication strengths noted in more than 40% of subjects included social interest, humor, and memory for people, past events, and/or facts. Conclusions: Significant delays and impairment in speech-language were common, but the majority of those with SMS communicated using speech by age 6 years. Age was a significant factor for some aspects of hearing loss and communication. Neither hearing loss nor otitis media exacerbated language impairment. These results confirm and extend previous findings about the nature of speech, language, hearing, and otopathology in those with SMS.